NONLINEAR SEISMIC BEHAVIOR OF A HISTORICAL DAM FOR DIFFERENT SOIL GROUPS - Yetkin, Musa; Calayir, Yusuf; Sayin, Erkut; Karaton, Muhammet (Yildiz Technical Univ, 2018)
In this study, effect of soil flexibility on non-linear seismic response of historical Sultan Mahmut dam which is constructed as masonry arch dam type is investigated. Crest displacement and damage of the dam are evaluated. Smeared crack model which includes the strain softening is used in the nonlinear analysis for the behavior of dam material. Reservoir and soil domains are assumed to be linear elastic. Solid-fluid interaction is considered by Eulerian approach. For seismic input, artificial acceleration records are generated for four different soil groups (A, B, C and D) considering D2 seismic level. These records are acted in the stream direction to the dam-soil-reservoir system. Effect of soil flexibility on seismic response of the dam is evaluated for each soil group. ANSYS finite element program is used for the solutions.
Keywords: Solid-fluid interaction; smeared crack model; artificial acceleration records; nonlinear seismic analysis